Alteration in nucleosome structure induced by thermal denaturation. - Seligy, V L (1978)
Mononucleosomes prepared from goose erythrocyte nuclei exhibited limited heterogeneity with respect to number of electrophoretic components, histones and DNA composition. The components differ slightly in ionic strength induced self-association. Thermal denaturation of each component gave only two dominant, highly cooperative, melting transitions, T" and T"'. Urea and trypsin were used to establish the differential lability of these two transitions. Comparison of the morphologies of the mononucleosomes at various stages throughout the melting profile indicated that the 13.3 +/- 1.5 nm diameter mononucleosomes start to disrupt only in the latter half of transition T" and do not unfold until after reaching T"'. The resultant, open ended (17.4 +/- 2.2 nm diameter) toroids are still largely negatively staining and much more uniform in shape if fixed simultaneously with gluteraldehyde.